Pengaruh Gaya Kepemimpinan Demokratis dan Budaya Organisasi terhadap Komitmen Karyawan dengan Lingkungan Kerja sebagai Variabel Intervening di RS X Jakarta Pusat - Arga Parulian; Hasyim Ahmad; Anastina Tahjoo (Journal of Educational Innovation and Public Health, 2024)
Employee commitment in an organization is not just carrying out their duties and obligations as employees in accordance with their job descriptions, but doing their best with their thoughts, attention, ideas, and dedication to produce the best for the organization. The problem that occurred at X Hospital Central Jakarta was the decreasing employee commitment related to the lack of employee intensity to stay working for a long time at X Hospital Central Jakarta and there were still employees who left the work hours room with a percentage of 27%, thus reducing the overall performance of the hospital and the lack of supporting work facilities. The purpose of this study was to analyze the influence of democratic leadership style and organizational culture simultaneously on employee commitment mediated by the work environment. This research method is quantitative causality against 64 non-medical employees who have worked for at least 6 months at X Hospital Central Jakarta. The sampling method was total sampling. The data analysis method used was the Three Box Method and the Path Analysis Method with SEM AMOS. The results of the study found that democratic leadership style and organizational culture simultaneously have a positive effect on employee commitment with the mediation of the work environment, democratic leadership style does not affect employee commitment, democratic leadership style does not affect the work environment, organizational culture does not affect employee commitment, organizational culture has a positive effect on the work environment, the work environment has a positive effect on employee commitment. The implications of the study in theory will prove the influence of research variables and in managerial terms will further improve the system of facilities for work facilities and improve communication between leaders and employees in hospitals. Suggestions for the need for attention from the hospital management to improve work facilities and improve communication between leaders and employees.